Uterovaginal prolapse: the sociodemographic profile and reproductive health service uptake in a low resource setting, Calabar, Nigeria - Obinna, Njoku Charles; N., Njoku A.; E., Efiok E.; M., Eyong E. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Uterovaginal prolapse is a common gynaecological condition in low resource countries because of high prevalence of grand multiparity, low skilled attendant at delivery and low contraceptive usage. Objective of this study was to determine the prevalence, sociodemographic profiles, utilization of reproductive health services and delay in seeking medical care of patient with uterovaginal prolapse in Calabar, Nigeria. Methods: This was a retrospective study of women who presented with uterovaginal prolapse at University of Calabar Teaching Hospital, Calabar, Nigeria between 1st May 2009 and 1st June 2019. Patients case records were retrieved and analyzed. Statistical analysis was done using SPSS version 22. Results: The prevalence of genital prolapse was 0.3%. The mean age and parity were 60.19±8.71 years and 6.31±2.80, respectively. The mean duration of symptoms before presentation was 3.19±2.16 years. Genital prolapse was commonest among age group 60-79 years (52.8%), parity 5-9 (66.7%), post-menopausal (97.2%), primary education (55.6%) and farmers (47.2%). Grade 3 uterovaginal prolapse was the commonest grade (58.3%). Most patients (86.1%) had symptoms of genital prolapse for less than 5 years before seeking medical treatment. The majority of patients had no antenatal care during their pregnancies (80.6%), no skilled attendant at deliveries (86.1%) and no contraceptive use during their reproductive years (77.8%). Participants with lower parity (1-4) (p=0.03), higher educational level (p˂0.001) and teachers/civil servants (p=0.043) presented earlier (less than 1 year) to the hospital. Conclusions: There is poor utilization of reproductive health services among women who develop uterovaginal prolapse in study environment. Women with higher social status sought for help earlier. Increasing awareness of this condition and providing antenatal care, skilled birth attendants and contraceptive services will reduce the burden of this condition.